Java the complete reference - Schildt, Herbert (McGraw-Hill Education, 2019)
"Fully updated for Java SE 11, Java: The Complete Reference, Eleventh Edition explains how to develop, compile, debug, and run Java programs. Best-selling programming author Herb Schildt covers the entire Java language, including its syntax, keywords, and fundamental programming principles. You'll also find information on key portions of the Java API library, such as I/O, the Collections Framework, the stream library, and the concurrency utilities. Swing, JavaBeans, and servlets are examined and numerous examples demonstrate Java in action. Of course, the very important module system is discussed in detail. This Oracle Press resource also offers an introduction to JShell, Java's interactive programming tool. Best of all, the book is written in the clear, crisp, uncompromising style that has made Schildt the choice of millions worldwide." --
Includes index. - print version record
Keywords: Java (Computer program language); Internet programming; Java (Langage de programmation); Programmation Internet